Graph-analytical models of complex systems for state assessment “organism – environment” - Kozulia, T.V.; Kozulia, M.M. (Problems of Atomic Science and Technology, 2022)
Practicism in business is generally associated with obtaining high-performance goal-setting solutions. Cost reduction in the case of making a decision requires weight components identification in the object “state (environment) - system processes - system end state” associated with the structure or functionality of systems (processes), which themselves arbitrarily determine the target result. The works aim is to determine model type of a complex structured object of any purpose, which adequately reflects system state and interaction with the environment “(environment – system) – process – (system state – environment)” in a situation of varying degrees uncertainty. Assessment of systemic formation state is due to the grouping of methods, their complex application in the study of the interaction “system – environment”, which is determined by the corporative relations between the components. To solve the problem of quality assessment of such system objects, structural and graphical approach information and methodological support was offered as a set of methods. Практичність у бізнесі зазвичай пов’язана з отриманням високопродуктивних рішень для постановки цілей. Зниження витрат у разі прийняття рішення вимагає ідентифікації вагових компонентів у об’єкті “стан (середа) – системні процеси – кінцевий стан системи”, пов’язаному зі структурою або функціональністю систем (процесів), які самі довільно визначають цільовий результат. Мета роботи – визначити тип моделі складного структурованого об’єкта будь-якого призначення, який адекватно відображає стан системи і взаємодія з оточенням “(середа – система) – процес – (стан системи – середа)” в ситуації різного ступеня невизначеності. Оцінка стану системного утворення обумовлена угрупованням методів, їх комплексним застосуванням при вивченні взаємодії “система – середовище”, яке визначається корпоративними відносинами між компонентами. Для вирішення проблеми оцінки якості таких системних об’єктів, як комплекс методів, було запропоновано структурно-графічне обгрунтування інформаційно-методичного забезпечення.